GESTURE-VERBAL UTTERANCES FROM THE COGNITIVE PERSPECTIVE - Alla Martynyuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article develops the idea of speech and gesture as an integral system of generation of meaning viewing an individual's cognitive system as a dynamic, evolving semantic lattice organising semantic items of propositional and imagistic modes around a core meaning: linguistic items (propositions) are linked to ideas, concepts and beliefs as well as to specific feelings, mental states, images of gestures and stereotypic patterns of behaviour. Since gesture and speech are equally engaged in generation of meaning, they are treated in terms of gesture-verbal utterances as minimal material carriers of semantic content, activating the semantic lattice. According to the sphere of human consciousness / sub-consciousness which is basically 'responsible' for their production and interpretation, gesture-verbal utterances are divided into rational classifying / qualifying (activating semantic structure to provide information, helping classify or qualify the referents of the utterances), emotional (activating emotional attitudes) and suggestive (activating no semantic content but organising narration over large spans). Rational gesture-verbal utterances are further classified on the basis of the semiotic principle, governing the gestural activation of semantic structure, into deictic (pointing to the referent), iconic (depicting the referent) and symbolic (standing for the referent) and also into literal and metaphoric in accordance with the image-realistic or image-schematic principle of depicting the referent.